2016
DOI: 10.9734/bjpr/2016/29317
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Anti - Herpes Activity of Selected Medicinal Plants Cited for Management of HIV Conditions in Kakamega County – Kenya

Abstract: Aim: To determine safety and anti-herpes activity of selected medicinal plants cited by Community Health Workers in Mukhwa sub-location, Bukaya location in Kakamega County, Kenya. Study Design: Ethno-medical interview for selection of medicinal plants and In-vitro experiment for determination of safety and anti-herpes activity. Methodology: Eight medicinal plants were selected for safety and determination of anti-herpes activity of water extracts using Vero cell and Human herpes Virus type 1. The metabolism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…[23] explained that many microbial infections cause the cells to release the highly oxidative molecules due to enhanced metabolism of oxygen leading to extensive damage to cells and tissues. The anti HSV findings by Radol et al [3] is consistent with the results on the basis of synergistic support provided by antioxidants in the in vivo mice experimental model.…”
Section: Phytochemical Screening Of Extracts For Common Pharmacologicsupporting
confidence: 80%
See 3 more Smart Citations
“…[23] explained that many microbial infections cause the cells to release the highly oxidative molecules due to enhanced metabolism of oxygen leading to extensive damage to cells and tissues. The anti HSV findings by Radol et al [3] is consistent with the results on the basis of synergistic support provided by antioxidants in the in vivo mice experimental model.…”
Section: Phytochemical Screening Of Extracts For Common Pharmacologicsupporting
confidence: 80%
“…The terpenoid groups are known for their interferon induction and some derivatives such as glycerrhetinic acid have been associated with HSV inhibition [25]. From these results it can be concluded that the high content of flavonoids and phenols in G. buchananii accounts for its antioxidant activity in the current report as well as anti HSV activity as reported by Radol et al [3].…”
Section: Table 1 Responses To Knowledge Of Hiv Conditions and Statussupporting
confidence: 71%
See 2 more Smart Citations
“…The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT, Sigma, USA) assay reported by Radol et al, [25] was used to determine the cytotoxic effects of the plant extracts on Vero cell lines. The cells were cultured in T-75 cell culture flasks and incubated in Eagle's Minimum Essential Medium (MEM) with 10% fetal bovine serum (FBS) at 37°C in 5% CO 2 .…”
Section: Cytotoxicitymentioning
confidence: 99%